Teacher's identity: an attempt to describe a territory - Cristián Desbouts (Universidad Politécnica Salesiana, 2012)
Teachers should care for the emotional stability of their students, teachers must take on the work of social workers, teachers have to answer to those problems caused by the difficult socio-economic situation facing our students... Today, phrases like these are common in discussions among teachers and non-teachers. All of them, one way or another, relate to teacher's identity, and all are trying to tell their own truth about what is like being a teacher today. Obviously, not all refer to the processes of learning or teaching learning problems. What is then the identity of a teacher? What does the word "teacher" encapsulate in its meaning in today's society? We will try to make an approach to the definition of a teacher's identity but not looking for a single, dogmatic definition, but by highlighting some landscapes that will identify this territory. Our position will be, therefore, that of a cartographer trying to peer into the world through his own observations (provided he has the ability to travel to the land he is trying to represent), or with data from narratives of those who have traveled there already, or through representations made by others before him. Certainly, like any map, our representation will not be a finished product , but an attempt to present to other man and woman signs to orientate themselves in this new territory and that they themselves will enrich with their personal contributions.